Periodontitis y aterosclerosis carotídea evaluadas mediante radiografías panorámicas en una población adulta y adulto mayor: Periodontitis and carotid atherosclerosis evaluated by panoramic radiographs in an adult and elderly population - Rivera-Ramírez, Roy Anthony (2023)
Objetive: To determine the relationship between periodontitis and carotid atherosclerosis through the use of panoramic radiographs of patients treated in Tacna 2020. Methods: Of 186 panoramic radiographs where carotid atherosclerosis is evidenced, the presence of periodontitis is shown by prolonged bone resorption taking as reference the dental root. Results: The presence of carotid atherosclerosis was found in 18.3% of the patients. The relationship between periodontitis and atherosclerosis is significant. On the other hand, no significant relationship was found between the extent of periodontitis and carotid atherosclerosis. It is limited that older adults have a significant relationship with carotid atherosclerosis. On the contrary, no significant relationship was found in gender. Conclusion: The relationship between periodontitis and carotid atherosclerosis through panoramic radiographs of patients older than 29 years of Tacna is significant.